Avaliação diagnóstica e prova semestral: a interlocução entre a SME e a DRE para a proposição de ações formativas - Fratelli, Minéa Paschoaleto (2018)
The present work investigates how the Avaliação Diagnóstica and the Prova Semestral, elaborated by the São Paulo Municipal Department of Education, are appropriated by the intermediary agency, the Regional Board of Education, in view of two focuses: the educational system in a macro view and the school in a micro vision. From this perspective, the question arises as to how the appropriation and reflections on these evaluations are carried out, such as the work carried out by the DRE through the provision of materials on external evaluation, organization of pedagogical bulletins, training of management teams, teacher training and the work carried out by the school, which indicate what students have learned and what they need to learn. The appropriation of this evaluation instrument and the results of these evaluations becomes essential in a formative evaluation perspective and in the processes of regulation of teaching and learning in order to improve student performance and guarantee learning rights. It is known that there are several advances in the implementation of an evaluation policy, but the qualification of this is directly linked to the systemic character of the action. The approach used in the study is qualitative research. It is based on a bibliographical research - with a documentary study to know the history of the external evaluation system in the country and in the Municipal Department of Education - in addition to the materials produced by the SME and the DRE, for the formations that deal with the processes involved in the evaluation, which underpin this study. In addition, from an exploratory survey, semi-structured interviews were conducted with the DRE training team to understand what reports do from external evaluations and what processes are carried out until decision making because of what students need to learn. The survey revealed coherence between what is produced by the SME and the action that the DRE plans for schools, but indicates the necessary investment in decision making beyond the interpretation of the data